Service quality, satisfaction and student loyalty in Malaysian private education - Mansori, Shaheen; Vaz, Anthony; Mohd Ismail, Zarina Mizam (Canadian Center of Science and Education, 2014)
The changing of the global demographic trends clearly suggests a growing demand for a quality higher education. In fact, several studies have been carried out in the past few years to explore the factors that have effects on the customer satisfaction and its consequences in various industries. In the same manner, this study also explores the five factors of service quality (SERVQUAL) and their relationship with the level of student satisfaction and their loyalty as well as the intervening role of satisfaction in the relationships between SERVQUAL factors and loyalty among undergraduate students. The study used self-administered questionnaires to test the proposed model and data collected from 460 questionnaires were analysed. The questionnaires were distributed at various private universities and colleges in Malaysia based on convenience sampling. The results of this study are in accordance with prior studies in this field as SERVQUAL factors do influence the level of customers’ satisfaction in the service industry. This study shows that the level of students overall satisfaction is mostly affected by tangibility. This finding indicates that the physical facility on the campus plays a major role in satisfying the students. The results also show that tangibility has the highest influence (directly and indirectly) on the students’ intention to continue to a higher level of studies and/or spreading good word of mouth about the institution to their friends and the society. However, to generalize the results of this study, consideration should be made to the limitation of the number of the private institutions where the samples are collected. It is suggested that for further study, more samples should be taken from a larger number of institutions.